Exploring EFL teachers’ perceptions of the use of peer assessment in external exam-dominated writing classes - Meletiadou, Eleni; Tsagari, Dina (MDPI, 2022)
Several studies on peer assessment (PA) have highlighted significant benefits for the learning process such as increased student motivation, enhanced collaborative learning (especially in terms of EFL writing) and improved reflection skills. Research on secondary school teachers’ perceptions of PA is lacking, particularly in English as a Foreign Language (EFL) external-examination-dominated contexts. The current study presents an in-depth exploration of 40 EFL Greek Cypriot teachers’ perceptions of the use of PA in secondary education to address adolescent learners’ poor writing performance, low motivation, and exam failure. Teachers used PA of writing for one whole school year with more than 400 students after receiving training in PA methods and continuous support throughout this implementation. The researcher used semi-structured interviews to explore EFL teachers’ attitudes towards PA after implementing it in their classes. Findings indicated that teachers were initially reluctant to use PA with their students but changed their minds during its implementation and reported that PA facilitated learning by making the educational process easier for learners. Given teachers’ favourable attitudes towards PA after experimenting with it for a whole year and the benefits that they believe students (especially low-achieving) may gain from the implementation of PA of EFL writing in their classes, this study suggests that PA is a promising inclusive assessment method that caters to diverse learners’ needs and fosters autonomy.